Total mesorectal excision and sphincter preservation - the early steps of rectal cancer surgery - Perez,Rodrigo O. (2014)
The treatment of rectal cancer has evolved significantly over the last 100 years. Standardization of total mesorectal excision and the development of techniques for sphincter preservation have resulted in significant improvements in the management of this disease. Still, local disease control and functional outcomes of sphincter preserving procedures remain a relevant issue. In this historical paper, the oncological and functional outcomes of patients with rectal cancer treated between 1960 and 1971 by a pioneer woman surgeon using a sphincter preserving approach and a technique resembling total mesorectal excision performed at that time are reported. The results reflect one of the earliest steps of partial intersphincteric resection and total mesorectal excision with good oncological outcomes (2% local recurrence) and acceptable functional outcomes in a highly selected group of patients.